SOCIAL-PSYCHOLOGICAL THEATER AS A MEANS OF PREVENTION OF ADOLESCENT ALCOHOLISM - Шатило, Юлія Петрівна; Новікова, Наталія Євгенівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article analyzes and presents for consideration the data of the research conducted to identify the main causes of alcohol consumption by minors in modern society. The sample of the study was made by students of 14-16 years. The total number of respondents was 59. The study was conducted in educational institutions of Bucha (Kyiv region) and the village of Pryvority (Zhytomyr region, Korishyshiv district). The student surveys were conducted through self-completion of questionnaires. The theoretical aspects of adolescent alcoholism, which is a negative social phenomenon, requires research and effective prevention. An analysis of the causes of alcohol abuse by adolescents showed that for most teenagers, it is a sense of independence and confidence; imitation of peers, older friends, parents; opportunity to forget about your problems, get distracted; feelings of joy, mood enhancement, happiness; the opportunity to "become older"; ability to make contacts more quickly and easily, make new friends. We have analyzed the theoretical foundations of the methodology of organizing social and psychological theater as a means of preventing the occurrence of causes of alcohol use among adolescents, which aims to perform the following tasks: to create conditions for the minor to reflect on his situation and his own behavior; invaluability in the approach to the analysis of adolescent behavior; creation of success in the activity; the removal of the teenager from the position of the child in the position of an adult, which involves not only learning new ways of communication, interaction with the environment, but also taking responsibility for actions and actions. The power of emotional and ideological-psychological influence of social-psychological theater makes it one of the most effective social-pedagogical and psychological means of formation of adolescents' value orientations, creation of conditional reality in which adolescents learn to identify and develop their needs, interests, common interests